INVESTIGATION OF Ge SUBSTRATES FOR MCT GROWN BY MOLECULAR-BEAM EPITAXY - A. L. Sizov; I. D. Burlakov; N. I. Yakovleva; E. D. Korotaev; A. E. Mirofyanchenko (Тонкие химические технологии, 2013)
Methods of chem-mech polishing and chemical etching were described, and characteristics of Ge wafers were investigated corresponding to technical requirements of MBE growth. Investigation methods included optical microscopy, X-ray diffraction analysis, high-resolution diffraction analysis, AFM and IR-Fourier microscopy.